Far lateral microdiscectomy: a minimally-invasive surgical technique for the treatment of far lateral lumbar disc herniation - Phan, Kevin; Dunn, Alexander E.; Rao, Prashanth J.; Mobbs, Ralph J. (Journal of Spine Surgery; Vol 2, No 1 (March 01, 2016): Journal of Spine Surgery, 2016)
umbar disc herniation arises when the annulus fibrosus of the vertebral disc fails, thus allowing displacement of the nucleus pulposus and other tissue. The term far lateral is used variably in the literature and usually refers to an extraforaminal displacement in the peridiscal zone peripheral to the sagittal plane of the most lateral part of the pedicle at the same level. Non-surgical treatments of far lateral disc herniation include physical therapy, anti-inflammatory medication, and corticosteroid injections. Where these conservative measures fail, surgical intervention may be required. Several surgical techniques for the treatment of far lateral herniations have been investigated, including total or medial facetectomy, laminectomy, hemilaminectomy, approaches through the pars interarticularis, and lateral approaches between the transverse processes via the intertransverse muscle and ligament. We present our far lateral microdiscectomy technique which involves accessing the nerve root lateral to the foramen through a small paramedian incision and use of an operating microscope. Far lateral microdiscectomy offers the prospect of better long-term results than other surgical techniques because of less extensive muscle dissection and preservation of the integrity of the facet joint.